PENGARUHKUALITAS PRODUK DANPERSEPSI HARGA TERHADAP KEPUTUSANPEMBELIAN KONSUMENSEPEDA MOTORMEREKHONDA (Studi pada MahasiswaPengguna Sepeda MotorHonda Vario di UnisbankSemarang) - Kenny Rubiharyanto, 09.05.51.0056; Soliha, Euis (Students Journal of Economic and Management, 2014)
The purpose of this study was to analyze the effect of product quality and perceived price on purchase decisions Unisbank student Semarang Vario Honda motorcycles. The population in this study is the user Vario Honda motorcycles. The samples in this study were students at the University Stikubank (Unisbank), Jl. Tri Lomba Juang dan Jl. Kendeng V Bendan Ngisor, Semarang, userâs Honda Vario. The samples in this study using a non-probability sampling with the sampling method used was purposive sampling, the sampling technique with a specific purpose. The analytical tool used is multiple linear regression analysis. The results of the analysis can be concluded that : (a) the quality of the products has a positive effect on purchasing decisions on the purchase of student Unisbank Semarang Vario Honda motorcycles. (b) perceived price has a positive effect on purchasing decisions on the purchase of student Unisbank Semarang Vario Honda motorcycles. Keywords: qualityof product, priceperceptions and purchasedecisions